2008 58th Electronic Components and Technology Conference 2008
DOI: 10.1109/ectc.2008.4550198
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of drop impact survivability of a 3D CSP stack module

Abstract: Chip scale packages (CSPs) are widely used in miniaturized electronic systems, and the performance advantages and reliability of single layer packages have been well studied for consumer applications. Three dimensional stacked modules allow for further miniaturization while retaining manufacturability and performance advantages, but they are not yet as widely used or investigated as single layer packages. Of particular concern is the survivability of a board mounted, stacked module under board level drop impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…The comparison of the 2 figures implies that a larger k (i.e., the solders act stiffer) results in a smaller solder stress oscillating at a higher frequency. Intriguingly, either from the numerical results in Figure 4 or from our previous calculations [2,9], we verified that the stresses in solders under a 0° drop could be so high as to reach one order of magnitude larger than that in the 90° drop, but oscillates at a much lower frequency. This comparison also indicates that the system acts more compliantly in the 0° drop than in the 90° drop, the same as was observed in the stress-wave propagation stage (but different in the underlying physics).…”
Section: Solder Joint Response To Board Vibrations -0° Versus 90° Drosupporting
confidence: 66%
See 1 more Smart Citation
“…The comparison of the 2 figures implies that a larger k (i.e., the solders act stiffer) results in a smaller solder stress oscillating at a higher frequency. Intriguingly, either from the numerical results in Figure 4 or from our previous calculations [2,9], we verified that the stresses in solders under a 0° drop could be so high as to reach one order of magnitude larger than that in the 90° drop, but oscillates at a much lower frequency. This comparison also indicates that the system acts more compliantly in the 0° drop than in the 90° drop, the same as was observed in the stress-wave propagation stage (but different in the underlying physics).…”
Section: Solder Joint Response To Board Vibrations -0° Versus 90° Drosupporting
confidence: 66%
“…The dynamics of an S-CSP module under JEDECcompatible board-level drop testing has been characterized in [2] by showing that the corner-most joints at the bottom (ballout) level of the package are the most vulnerable to drop impact. The results also showed that those critical solder joints are likely to experience plastic yield as early as in the first tens of microseconds after impact inception, during which the impact-induced stress-wave propagation dominates the dynamics of the board-mount stacked-CSP assembly.…”
Section: Introductionmentioning
confidence: 99%